Reproductive stage physiological and transcriptional responses to salinity stress in reciprocal populations derived from tolerant (Horkuch) and susceptible (IR29) rice - Razzaque, Samsad; Haque, Taslima; Elias, Sabrina M.; Rahman, Md. Sazzadur; Biswas, Sudip; Schwartz, Scott; Ismail, Abdelbagi M.; Walia, Harkamal; Juenger, Thomas E.; Seraj, Zeba I. (Springer, 2017)
Global increase in salinity levels has made it imperative to identify novel sources of genetic variation for tolerance traits, especially in rice. The rice landrace Horkuch, endemic to the saline coastal area of Bangladesh, was used in this study as the source of tolerance in reciprocal crosses with the sensitive but high-yielding IR29 variety for discovering transcriptional variation associated with salt tolerance in the resulting populations. The cytoplasmic effect of the Horkuch background in leaves under stress showed functional enrichment for signal transduction, DNA-dependent regulation and transport activities. In roots the enrichment was for cell wall organization and macromolecule biosynthesis. In contrast, the cytoplasmic effect of IR29 showed upregulation of apoptosis and downregulation of phosphorylation across tissues relative to Horkuch. Differential gene expression in leaves of the sensitive population showed downregulation of GO processes like photosynthesis, ATP biosynthesis and ion transport. Roots of the tolerant plants conversely showed upregulation of GO terms like G-protein coupled receptor pathway, membrane potential and cation transport. Furthermore, genes involved in regulating membrane potentials were constitutively expressed only in the roots of tolerant individuals. Overall our work has developed genetic resources and elucidated the likely mechanisms associated with the tolerance response of the Horkuch genotype.